Investigating the influence of business intelligence on the quality of decision making in an Indonesian fertilizer company - Urumsah, Dekar; Ramadhansyah, Heri (Journal of Contemporary Accounting, 2019)
This study investigates the factors influencing the quality of decision making in Indonesian fertilizer sector. Business intelligence management, business intelligence scope, data quality, content quality, and information quality are the examined factors. Empirical study was conducted through survey questionnaire from top and operational managers who operated a business intelligence system. A structural equation modelling using Partial Least Square is condected through the analysis of 111 usable the questionnaires. The results of the study show that business intelligence management is the main factors influencing the quality of decision making. The study contributes to both academia and industry by provide new insights for managers regarding to the influence of business intelligence on the high quality of decision making. This could serve as a guideline for organizations in understanding the important factors that should be considered when deciding to improve the quality of decision making.